Double-Dose Ranibizumab for Eyes with Refractory Exudative Age-Related Macular Degeneration - Modjtahedi, Bobeck S.; Morse, Lawrence S.; Rashid, Saadia; Park, Susanna S. (Journal of Ocular Diseases and Therapeutics, 2013)
In this retrospective chart review of the 10 eyes (8 subjects) with exudative age-related macular degeneration that had persistent macular fluid on spectral-domain optical coherence tomography (SD-OCT) [after at least 3 monthly intravitreal ranibizumab (0.5mg) or bevacizumab (1.25mg)], central macular thickness was significantly lower after 2 monthly double-dose intravitreal ranibizumab injections (0.1mg, DDR) (324 + 77µm at baseline vs 248 + 50µm, P=0.02). Seven of 10 eyes that received DDR had some qualitative anatomic improvement on SD-OCT with the first 2 DDR, but no further OCT improvements were noted thereafter with additional DDR. The DDR treatment effect was transient in 3 of 7 eyes despite sustained DDR treatment. Best corrected visual acuity remained stable in 7 of 10 eyes over the initial period of DDR (first 2-3 injections), 2 eyes improved > 2 lines and 1 eye had > 2 lines of worsening. The improvement in BCVA did not correlate with improvement noted on SD-OCT. Paracentesis was performed frequently for acute intraocular pressure elevation or as prophylaxis in eyes receiving DDR due to the higher volume injected intravitreally but no other ocular or systemic adverse effect was noted with DDR.